The yeast SLY gene products, suppressors of defects in the essential GTP-binding Ypt1 protein, may act in endoplasmic reticulum-to-Golgi transport. - Ossig, R (1991)
It has been shown previously that defects in the essential GTP-binding protein, Ypt1p, lead to a block in protein transport from the endoplasmic reticulum (ER) to the Golgi apparatus in the yeast Saccharomyces cerevisiae. Here we report that four newly discovered suppressors of YPT1 deletion (SLY1-20, SLY2, SLY12, and SLY41) to a varying degree restore ER-to-Golgi transport defects in cells lacking Ypt1p. These suppressors also partially complement the sec21-1 and sec22-3 mutants which lead to a defect early in the secretory pathway. Sly1p-depleted cells, as well as a conditional lethal sly2 null mutant at nonpermissive temperatures, accumulate ER membranes and core-glycosylated invertase and carboxypeptidase Y. The sly2 null mutant under restrictive conditions (37 degrees C) can be rescued by the multicopy suppressor SLY12 and the single-copy suppressor SLY1-20, indicating that these three SLY genes functionally interact. Sly2p is shown to be an integral membrane protein.